EDU KRISZA (KRITERIA JAJANAN SEHAT BEBAS ZAT ADITIF) KULINER LOKAL KUE BANJAR - Andhika Mayasari; Noer Af’idah; Oktaffi Arinna Manasikana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The characteristics of healthy snacks are containing healthy nutrition criteria, clean, and free from harmful additives, so it is safe to consume. Banjar cake is a sweet and crunchy cake made from glutinous rice flour with original flavors, chocolate and ginger. So, this community service entitled